2015
DOI: 10.1523/jneurosci.4115-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Action of Dendritic Mitochondria and Creatine Kinase Maintains ATP Homeostasis and Actin Dynamics in Growing Neuronal Dendrites

Abstract: The distribution of mitochondria within mature, differentiated neurons is clearly adapted to their regional physiological needs and can be perturbed under various pathological conditions, but the function of mitochondria in developing neurons has been less well studied. We have studied mitochondrial distribution within developing mouse cerebellar Purkinje cells and have found that active delivery of mitochondria into their dendrites is a prerequisite for proper dendritic outgrowth. Even when mitochondria in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 75 publications
6
65
0
Order By: Relevance
“…Taken together, the PS1 P117L AD neurons reproduce major characteristics observed in neurons in AD brain, and are useful for understanding molecular mechanisms of AD pathology in neurons. Many studies have shown the role of mitochondria on neuritogenesis through calcium handling and ATP production4344. Recently, we demonstrated that 8-oxoG accumulation in neuronal mtDNA results in mitochondrial dysfunction, and leads to poor neurite outgrowth with decreased complexity of neuritic arborization, using isolated cortical neurons from mice lacking both 8-oxo-dGTP-depleting MTH1 and 8-oxoG excising OGG130, similar to the AD model neurons.…”
Section: Discussionmentioning
confidence: 81%
“…Taken together, the PS1 P117L AD neurons reproduce major characteristics observed in neurons in AD brain, and are useful for understanding molecular mechanisms of AD pathology in neurons. Many studies have shown the role of mitochondria on neuritogenesis through calcium handling and ATP production4344. Recently, we demonstrated that 8-oxoG accumulation in neuronal mtDNA results in mitochondrial dysfunction, and leads to poor neurite outgrowth with decreased complexity of neuritic arborization, using isolated cortical neurons from mice lacking both 8-oxo-dGTP-depleting MTH1 and 8-oxoG excising OGG130, similar to the AD model neurons.…”
Section: Discussionmentioning
confidence: 81%
“…The importance of Cr in brain development has been highlighted in a recent study showing that the loss of Cr kinase leads to aberrant neuronal development. 35 In addition, maternal Cr supplementation in rats enhanced hippocampal neuron development and improved long-term potentiation. 36 Taken together, these data suggest that using Nestin-cre mice to generate brain-specific Slc6a8 disruption is more comparable to the ubiquitous Slc6a8 −/y mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cell intrinsically, mitochondrial respiration and energy metabolism is a potential candidate, as mitochondrial function is directly dependent on iron and is also critical for dendrite growth [9]. Abnormalities in hippocampal energy metabolism have been documented in the IDA rat while iron-deficient [13,24,56] and in adulthood long after iron repletion [57].…”
Section: Discussionmentioning
confidence: 99%